An exploration of the conditions for deploying self-management strategies: a qualitative study of experiential knowledge in depression - Smit, Dorien (BMC Psychiatry, 2020)
BACKGROUND: Living with recurrent, and/or chronic depression requires long-term management in addition to active coping on a day-to-day basis. Previous research on long-term management, and coping with depression mainly focused on identifying self-management strategies. However, research on the conditions for deploying self-management strategies in depression is lacking. By means of exploring the development of experiential knowledge in depression, and its relation with coping with depression, this study aims to gain insight into the conditions for deploying self-management strategies. METHODS: In the current qualitative study, individual pathways to recovery, living with depression, and recurrence risk were assessed, including but not limited to long-term management. ‘Experiential knowledge’, which can be defined as patients’ unique knowledge and own lived experiences in facilitating and debilitating factors in the recovery process and coping with the disorder, was used as a sensitizing concept. Thirteen semi-structured interviews were conducted with individuals who experienced at least two depressive episodes and were currently in (partial) remission, plus two deviant cases were interviewed to check for saturation. Until saturation was achieved, participants were purposively selected to include diverse perspectives on coping with depression. Data were analysed using a narrative research method. RESULTS: The results show that deploying self-management strategies are an integral part of ‘experiential knowledge’. The evolvement of experiential knowledge can be seen as a cyclical process of the main themes that were identified as relevant when coping with depression: introspection, empowerment, self-management strategies, and external moderators of the environment. The identification of supporting and impeding factors in coping with depression from a patient perspective might increase a sustainable use of self-management strategies. CONCLUSION: These results highlight the need for an individualised holistic model of coping with depression, both in research, and in practice. By means of integrating experiential knowledge in this holistic approach, the conditions for deployment of self-management strategies in depressive patients can be specified.